Involvement of the submandibular gland in oral squamous cell carcinoma patients with positive lymph nodes - Yang, S.; Su, J.-Z.; Gao, Y.; Yu, G.-Y. (Journal of stomatology, oral and maxillofacial surgery, 2020)
No consensus exists about submandibular glands (SMGs) involvement in oral squamous cell carcinoma (OSCC) patients with cervical lymph node metastasis. We aimed to investigate the prevalence of SMG involvement in OSCC patients with positive lymph nodes. Retrospective analysis of data of 302 study subjects with positive lymph nodes in OSCC operated between January 2002 and December 2012. Only 1/302 (0.3%) study subject had SMG involvement. The mode of spread was by direct extension of the primary carcinoma. Extracapsular spread of level IB lymph nodes was seen in 12/302 (4%) patients. Only one of these patients had involvement of the fibrous tissue around the SMG. SMG involvement is very rare in OSCC patients with cervical lymph node metastasis. Preservation of the ipsilateral SMG during neck dissection might be oncologically safe when involvement by direct spread is unlikely.